Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.31887/dcns.2020.22.2/gsmall
|View full text |Cite
|
Sign up to set email alerts
|

Brain health consequences of digital technology use

Abstract: Emerging scientific evidence indicates that frequent digital technology use has a significant impact—both negative and positive—on brain function and behavior. Potential harmful effects of extensive screen time and technology use include heightened attention-deficit symptoms, impaired emotional and social intelligence, technology addiction, social isolation, impaired brain development, and disrupted sleep. However, various apps, videogames, and other online tools may benefit brain health. Functional imaging sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 55 publications
1
76
0
3
Order By: Relevance
“…The rapid development of digital technologies has transformed societies across the world [ 1 , 2 ]. Access to electronic devices and the internet exposes our minds to virtual computer-generated worlds, which greatly impact our daily lives [ 3 , 4 , 5 ]. If exposure to virtual realities is subordinate to achieving long-term personal goals, digital technologies are able to improve the overall well-being of healthy individuals [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of digital technologies has transformed societies across the world [ 1 , 2 ]. Access to electronic devices and the internet exposes our minds to virtual computer-generated worlds, which greatly impact our daily lives [ 3 , 4 , 5 ]. If exposure to virtual realities is subordinate to achieving long-term personal goals, digital technologies are able to improve the overall well-being of healthy individuals [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with Horowitz-Kraus and Hutton [22], who found that increased screen time was associated with poorer executive functioning in very young children. In a systematic review, Small et al also found that frequent tablet use might negatively affect brain function and behavior [3]. All these findings have jointly confirmed that tablet use has adversely impacted young children's executive function.…”
Section: 'Non-user' Outperformed 'Heavy-user' Group In the Dccsmentioning
confidence: 88%
“…They have also underscored the difficulties in finding studies directed to the desired age and type of electronic device, which is a potential cause of bias. Small et al conducted another systematic review and reported harmful effects such as heightened attention-deficit symptoms, impaired emotional and social intelligence, technology addiction, social isolation, impaired brain development, and disrupted sleep [3]. Meanwhile, they also found that various apps, videogames, and other online tools might benefit brain health in adulthood.…”
Section: 1tablet Use and Early Childhood Developmentmentioning
confidence: 99%
See 2 more Smart Citations